2006
DOI: 10.1300/j003v20n01_02
|View full text |Cite
|
Sign up to set email alerts
|

The Community Reintegration Project: Occupational Therapy at Work in a County Jail

Abstract: The incarcerated population in U.S jails has more than doubled in the last thirty years while prison populations have quintupled. Over half of those released from incarceration return to correctional systems within one year of release. One of the reasons for these high rates of recidivism is that many inmates lack the community living skills necessary for community reintegration. Successful community reintegration for ex-offenders requires a skill set that occupational therapists have long addressed in their d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…Barriers to meaningful occupation in the forensic setting can be understood in terms of occupational risk factors, including concepts such as occupational deprivation (Cronin‐Davis et al. , 2004; Duncan, 2008; Eggers, Munoz, Scuilli & Crist, 2006; Molineux & Whiteford, 1999; Whiteford, 1997; Wilcock, 2006). Occupational imbalance, a development of the popular concept of work‐life balance, focusses on time use (Backman, 2004), with implications for the routines and opportunities of institutional life.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers to meaningful occupation in the forensic setting can be understood in terms of occupational risk factors, including concepts such as occupational deprivation (Cronin‐Davis et al. , 2004; Duncan, 2008; Eggers, Munoz, Scuilli & Crist, 2006; Molineux & Whiteford, 1999; Whiteford, 1997; Wilcock, 2006). Occupational imbalance, a development of the popular concept of work‐life balance, focusses on time use (Backman, 2004), with implications for the routines and opportunities of institutional life.…”
Section: Introductionmentioning
confidence: 99%
“…Of the five most frequently reported client goals, three in particular have an obvious occupational focus: productivity, instrumental activities of daily living and activities of daily living (IADL/ADL), and life/leisure engagement. Providing clients opportunities for meaningful work and vocational rehabilitation prior to discharge may reduce recidivism and promote successful community transition (Eggers et al ., ). Fittingly, as respondents perceived advocacy for the occupational therapist role at the organizational and policy levels to be vital, this advocacy work may be accomplished by focusing on client occupational engagement and participation in personally relevant roles (Bacon et al ., ; Gooch and Living, ; Stelter and Whisner, ), which may protect against criminal activity (Dunn and Seymour, ).…”
Section: Discussionmentioning
confidence: 97%
“…It follows then, that research should be undertaken to ascertain the impact of occupational therapy on meaningful outcomes such as recidivism rates and community reintegration (Eggers et al ., ; Young et al ., ). Strategically, forensic occupational therapists will need to exhibit the value of their role to stakeholders, as governments and funding agencies are necessitating outcome delivery above mere service delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the occupational therapy educational elements of this study, however, compare with those found in the Eggers et al . () paper, but the two programs used different techniques to deliver their interventions.…”
Section: Discussionmentioning
confidence: 99%